Investigating myelin oligodendrocyte glycoprotein antibodies in hereditary citrullinemia. (March 2022) - Oncel, Ibrahim; Yousefi, Mohammadreza; Inci, Asli; Gulten, Zumrut Arslan; Kisa, Pelin Teke; Karaca, Meryem; Unal, Özlem; Gunduz, Mehmet; Kor, Deniz; Mungan, Neslihan Onenli; Arslan, Nur; Tumer, Leyla; et al.
Abstract: Metabolites like lipids, amino acids or peptides can affect the immune system. Citrulline is an amino acid that activates several inflammatory pathways. Serum citrulline levels are markedly elevated in hereditary citrullinemia type 1 (CTLN1), and cases with CTLN1 have have been described with inflammatory lesions of the central nervous system (CNS). This suggests the presence of a relatively proinflammatory state in CTLN1. We therefore tested sera of CTLN1 patients for anti-myelin oligodendrocyte glycoprotein (MOG) antibodies which are a frequent cause of inflammatory CNS disorders in young patients. Patients with CTLN1 (n = 15) and control groups consisting of phenylketonuria (n = 22), juvenile idiopathic arthritis (n = 13), pediatric onset systemic lupus erythematosus (n = 17) and healthy controls (n = 48) were tested for serum anti-MOG IgG and anti-MOG IgG1 antibodies in a live-cell based assay. Serum citrulline levels were elevated in 14/15 CTLN1 patients at the time of the study. No clear anti-MOG IgG positivity was detected in any of the CTLN1 or control groups. One CTLN1 and one healthy control case with anti-MOG IgG titers close to borderline were also tested for MOG-specific IgG1, with similar results. These findings did not support the role of elevated serum citrulline levels in facilitating antibody response against MOG. Other pathways that can be investigated in CTLN1 include lymphocytic responses against neural antigens or any direct effects of citrulline on neural tissue.